2019
DOI: 10.3390/cells8111369
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pregnancy-Specific Glycoprotein 1 With Integrin α5β1 Is a Modulator of Extravillous Trophoblast Functions

Abstract: Human pregnancy-specific glycoproteins (PSGs) serve immunomodulatory and pro-angiogenic functions during pregnancy and are mainly expressed by syncytiotrophoblast cells. While PSG mRNA expression in extravillous trophoblasts (EVTs) was reported, the proteins were not previously detected. By immunohistochemistry and immunoblotting, we show that PSGs are expressed by invasive EVTs and co-localize with integrin α5. In addition, we determined that native and recombinant PSG1, the most highly expressed member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 94 publications
2
29
0
Order By: Relevance
“…α5β1 promotes trophoblast adhesion and invasion by interacting with other molecules. For instance, the α5 subunit colocalizes and interacts with pregnancy-specific glycoprotein-1 to promote the adhesion of the EVTs to the decidual cells [28]. On the other hand, the β1 subunit associates with A disintegrin and metalloproteinase domain-8 (ADAM8) during the initial stages of cell-matrix attachment, suggesting that ADAM8 may enhance β1 subcellular localization to actin-rich structures or may regulate the configuration of β1 [29].…”
Section: Integrinsmentioning
confidence: 99%
“…α5β1 promotes trophoblast adhesion and invasion by interacting with other molecules. For instance, the α5 subunit colocalizes and interacts with pregnancy-specific glycoprotein-1 to promote the adhesion of the EVTs to the decidual cells [28]. On the other hand, the β1 subunit associates with A disintegrin and metalloproteinase domain-8 (ADAM8) during the initial stages of cell-matrix attachment, suggesting that ADAM8 may enhance β1 subcellular localization to actin-rich structures or may regulate the configuration of β1 [29].…”
Section: Integrinsmentioning
confidence: 99%
“…Second, the bound form of CEACAM enhances the KC microenvironment by activating fibroblasts, which in turn facilitate CRC growth (139,141). ECM expression of the α5β1 integrin/fibronectin interaction then leads to cell survival (142)(143)(144). Finally, CEACAM5 upregulates adhesion molecules such as E-cadherin and N-cadherin, thereby promoting aggregation (cell survival) and metastasis (139,140,(144)(145)(146).…”
Section: Liver Metastasis and Colorectal Cancermentioning
confidence: 99%
“…During adhesion of the late blastocyst to the endometrium, trophoblast cells begin to differentiate and invade the endometrium, the 1/3 of the uterine muscle layer and the vascular system, which ensures a sufficient blood supply to the placenta, maintaining normal embryo development ( 1 , 2 ). Previous studies have revealed that an invasive insufficiency of trophoblast cells can lead to the occurrence of preeclampsia ( 3 , 4 ). Moreover, it has been shown that hypoxia can lead to an insufficiency in invasion in the trophoblast cells ( 1 ).…”
Section: Introductionmentioning
confidence: 99%